O acesso a cidadania pelas comunidades quilombolas através do fomento e do desenvolvimento de políticas públicas de igualdade: um estudo de caso - Passos, Rachel Aparecida de Aguiar (2021)
Appropriate access to citizenship by quilombola communities (communities initially founded by runaway groups of fugitive slaves) is attainable through the implementation of public policies of racial equality by the State. Quilombola communities are organizations of knowledge and traditions, built from the fight against racism, marked by the territorial resistance of black people, seeking the assertion of rights to preserve their way of life. They are a minority protected by the State through a legal framework founded on art. 68 of the ADCT – Ato das Disposições Constitucionais Transitórias (Transitory Constitutional Disposition Act) of the CRB/88 (Constitution of 1988) and public policies developed for this segment thereafter. This research analyses the implementation of public policies of racial equality and their role in the development of quilombola citizenship, avoiding the violation of rights and taking into consideration the specificities of these communities, for their proper social insertion. It is a qualitative research, of an exploratory nature, through a case study. To meet this objective, an analysis of racism as a social phenomenon and its influence on the current unequal distribution of rights is carried out, which reverberates in social tensions and in the struggle of black movements. Furthermore, it takes up the historical, cultural, social and political development of quilombola communities, elucidating their dilemmas. Then, it analyses the formation of public policies of racial equality and its implementation, by the three levels of government, based on a case study conducted in the quilombola community of Marinhos, located in the rural area of the city of Brumadinho-MG. A structured questionnaire was applied to 30 quilombola households, as well as interviews with 4 community leaders. Representatives of public authorities in the three levels of government were interviewed as well, through virtual media. Secondary data were also used, from different sources: IBGE (Brazilian Institute of Geography and Statistics), official documents (mainly of administrative procedure of the public defender's office – DPMG) and documents provided by the community itself. At last, it is evident a scenario of regression of public policies of racial equality and overcoming institutional racism, as well as the dismantling of institutions intended for quilombola communities since Programa Brasil Quilombola – PBQ (Brazil Quilombola Program), the transformation of SEPPIR (Department for Policies to Promote Racial Equality) into SNPIR (National Department for Policies to Promote Racial Equality) and the lowering of its status, until the very extinction of the theme in the PPA 2020-2023 (multiannual plan for 2020-2023). The current perspective shows the marginalization of communities in reaching citizenship.